Flu vaccine administered to health care personnel working with children at a private health provider: (2019-2020) (Archives of Pediatrics of Uruguay, 2023)
Introduction: the influenza virus infection causes morbidity and mortality. Health care personnel (HCP) is one of the priority groups to be vaccinated.Objective: to learn about HCP’s vaccination coverage against influenza of those workers working with children at CASMU in 2019 and 2020, and the reasons why they received vaccination or did not.Material and Methods: observational, descriptive, crosssectional study. Data collection in 2020: anon ymous survey. Variables: age, place of work (emer gency, hospital or clinic), function, risk of serious illness, vaccination received (or not received) in 2019 and 2020 and reasons.Results: 204 workers completed the survey; influenza vaccination: 73% in 2019 and 77.5% in 2020 (p>0.05). Montevideo‘s Emergency Department presented the highest level of vaccination and hospitalization (2019-90.7%; 2020-93%) followed by the Ciudad de la Costa’s Emergency Department. By occupational level: doctors: vaccination> 95% (2019 and 2020); graduates and nursing assistants: 2019-68.6%; 2020- 75.7%; administrative, kitchen, cleaning and gate house staff: 2019-33%, 2020-41%. The increase in vaccinated personnel in 2020 was not significant for any of the occupations. 21% of those surveyed had a risk of serious illness; 65% were vaccinated in 2019 and 74.4% in 2020. All the sampled pregnant women were vaccinated. The most frequent reasons mentioned for vaccination (2019 and 2020): “prevention” (50.5%), being PS (36%). Those who were not vaccinated stated that were “never ill” (19%). Those who had not received the vaccine in 2019, but received in 2020, mostly mentioned the “pandemic” as a reason.Conclusion: in CASMU, the percentage of health workers in contact with children who adhered to the flu vaccination in 2019 and 2020 was higher than 70%. There was no significant increase after to the pandemic. Coverage in polyclinics and nonmedical HCP, in particular those HCP with risk factors for serious diseases, should be improved.
Keywords: Influenza Vaccines; Health Personnel